Analisis Faktor-Faktor Yang Mempengaruhi Profitabilitas Bank Syariah Di Indonesia Tahun 2011-2014 - Sholihah, Mar'atush, Atwal Arifin, Drs., Akt.,M.Si (2016)
This research aims to test the factors that affect profitability syariah banks in indonesiaof 2011-2014. Factors that affects profitability ( ROA ) in this research namely Buying and Selling Financing, Profit Sharing Financing, Financing To Deposit Ratio, Non Performing Financing, And Capital Adequacy Ratio. Apopulation that used in this research was all a shariah bank financial released a report in Indonesian Bank. A method of the sample by means of purposive sampling according to the criteria .The total sample collected by 48.With the outliers about 9 and to 39 sample .The data has collected analyzed using data analysis who first done testing the classic prior to the testing of hypotheses .The testing of hypotheses in this research using analysis of multiple regression by test t , the f and coefficients determination. The results showed that the variable capital adequacy ratio effect on return on assets (ROA). This indicates that the great small capital can influence the Islamic banks in profit. While the variable buyying and selling financing, profit sharingfinancin, financing to deposit ratio, and non performing financing has no effect against the return on asset (ROA). This means a total lack of such variables do not have an impact on Islamic banks in profitability. Password:Buying and SellingFinancing , Profit SharingFinancing, Financing To Deposit Ratio , Non Performing Financing , Capital Adequacy Ratio , Return On Assets.